Effect of Ag target power on structure, mechanical properties of TaC–Ag films. Issue 8 (15th April 2022) - Hu, Jiaojiao; Li, Hang; Li, Jiangliang; Wu, Qiujie; Huang, Jiewen; Kong, Jian; Shi, Yan; Zhang, Guichang; Xiong, Dangsheng
Abstract: To achieve both hard and tough, Ag atoms with various contents were doped in Ta–C films. The microstructure, mechanical and tribological properties of TaC–Ag films were investigated and the strengthening effect of minimal Ag atoms on TaC–Ag films were explored. When the Ag target power is 8 W (∼1.18 at.% Ag), TaC–Ag film present FCC Ta(Ag)C solid solution phase. With increasing Ag target power from 12 to 30 W (∼9.35 at.% Ag), Ag free phases are separated from Ta(Ag)C phase, which is responsible for the results that the hardness of TaC–Ag film firstly increase then decreases with the increases of Ag doping content. High hardness (H∼49.0 GPa) and toughness (KIC ∼2.2 MPa m 1/2 ) is obtained from TaC–Ag8 film with the Ag target power of 8 W, while the hardness monotonically decreases to 9.8 GPa for TaC–Ag30 film with the target power of 30 W. The low wear rate of TaC–Ag8 film is attributed its high hardness and toughness, while the low friction coefficient (0.25) of TaC–Ag30 film is due to the lubrication of Ag phase and highly graphitized carbon.